Phenome-wide association study and functional annotation of hemoglobin A1c-associated variants in African populations - Chisom Soremekun; Oyesola Ojewunmi; Amarachukwu Nwagbata; Homa Bazireh; Sapna Sharma; Daudi Jjingo; David Patrick Kateete; Oyekanmi Nash; Harald Grallert; Chiara Batini; Annette Peters; Segun Fatumo (PLoS ONE, 2025)
Background Glycated hemoglobin (HbA1c) measures the average blood sugar level over the past three months. As a vital biomarker of blood glucose levels, it is used to diagnose Type-2 diabetes mellitus (T2D) and monitor glycemic control. A heritability estimate of 47% to 59% suggests that about half of the variation in HbA1c levels can be attributed to genetic factors. Despite African populations being the most genetically diverse and unique for fine-mapping, there is a paucity of data on the genetic drivers of HbA1c in African individuals. In this study, we performed functional annotation and a Phenome-Wide Association Study (PheWAS) of HbA1c-associated variants in two African populations. Method In this study, we utilized summary statistics of the HbA1c GWAS meta-analysis of 7,526 individuals from South Africa and Uganda to conduct a PheWAS using GWASATLAS. We also performed a functional analysis using the functional mapping and annotation (FUMA) tool. Single nucleotide polymorphisms (SNPs) were prioritized using the SNP2GENE function, while the gene expression patterns and shared molecular functions were explored in the GENE2FUNC. Result Three genome-wide significant loci were identified with the lead SNPs: rs6724428, rs148228241, and rs8045544 – mapped to GULP1, HBA1, and ITFG3 genes, respectively. The minor allele frequencies of rs148228241 (0.07) and rs8045544 (0.19) are rare or non-existent in non-African populations. Both rs8045544 and rs148228241 are significantly associated with the mean corpuscular hemoglobin concentration (MCHC). A lower MCHC is associated with alpha thalassaemia, resulting from deletions in HBA1 and HBA2 genes. Such deletions are prevalent in malaria-endemic regions of Africa due to their selective survival advantage. The rs6724428 variant is associated with skeletal functions, reflecting the link between glucose metabolism and bone mineral density. Discussion Our findings highlight the interplay between glucose metabolism, erythropoiesis, and skeletal health. The significant associations of HbA1c-variants with both skeletal function and MCHC underscore the potential of these variants to impact broader physiological processes. A large-scale study of African individuals will be essential to unravel genetic variants influencing HbA1c.